1990
DOI: 10.1001/jama.264.3.359
|View full text |Cite
|
Sign up to set email alerts
|

Effects of communitywide education on cardiovascular disease risk factors. The Stanford Five-City Project

Abstract: To test whether communitywide health education can reduce stroke and coronary heart disease, we compared two treatment cities (N = 122,800) and two control cities (N = 197,500) for changes in knowledge of risk factors, blood pressure, plasma cholesterol level, smoking rate, body weight, and resting pulse rate. Treatment cities received a 5-year, low-cost, comprehensive program using social learning theory, a communication-behavior change model, community organization principles, and social marketing methods th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
202
0
5

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(208 citation statements)
references
References 0 publications
1
202
0
5
Order By: Relevance
“…The proposal was deemed too costly, however, and the trial was never conducted. Large-scale multifactoral CVD risk factor interventions that were conducted include the Multiple Risk Factor Intervention Trial (Multiple Risk Factor Intervention Trial Research Group, 1990), the North Karelia Project (Puska, et al, 1985), the Stanford Three-City and Five-City Projects (Farquhar, et al, 1990), and the Pawtucket (Elder, et al, 1986) and Minnesota (Luepker, et al, 1994) Heart Health Programs. Youth multifactor interventions also were developed, with a movement toward comprehensive school health programs.…”
Section: Mhbc Intervention Research Studies Of Mhbc Interventions In mentioning
confidence: 99%
“…The proposal was deemed too costly, however, and the trial was never conducted. Large-scale multifactoral CVD risk factor interventions that were conducted include the Multiple Risk Factor Intervention Trial (Multiple Risk Factor Intervention Trial Research Group, 1990), the North Karelia Project (Puska, et al, 1985), the Stanford Three-City and Five-City Projects (Farquhar, et al, 1990), and the Pawtucket (Elder, et al, 1986) and Minnesota (Luepker, et al, 1994) Heart Health Programs. Youth multifactor interventions also were developed, with a movement toward comprehensive school health programs.…”
Section: Mhbc Intervention Research Studies Of Mhbc Interventions In mentioning
confidence: 99%
“…Some studies suggest that interventions which improve patient knowledge about hypertension may lead to controlled BP in the short term. [17][18][19] Severe uncontrolled hypertension was more common among patients who had no primary care physician and among those who were noncompliant with their antihypertensive medication regimens. 20 Previous work with hypertensive adults in a state Medicaid program 21 and in a Department of Veterans Affairs population 22 found that those terminated from their insurance program were found to have BP significantly worse than their baseline pressure prior to termination of these benefits.…”
mentioning
confidence: 99%
“…This study shared with the MHHP the goal of reducing car diovascular risk factors in entire adult populations and shared many features of the programs for adults (Farquhar et al 1990). The adolescent smoking feature of this study assessed whether reductions in cigarette smoking among adults were reflected among adolescents.…”
Section: Observations On Research On Multifaceted Educational Programsmentioning
confidence: 98%
“…Trials postdating the meta-analysis of Kottke and colleagues (1988) have also indicated that brief clini cal interventions have a small but reliable impact on smoking cessation success (Cummings et al 1989a;Risser and Belcher 1990;Taylor et al 1990;Ockene et al 1991Ockene et al , 1994Weissfeld and Holloway 1991;Hollis et al 1993;Strecher et al 1994). A meta-analysis of seven studies found that physician advice to quit increases cessation by 30 percent (Fiore et al 2000).…”
Section: Efficacymentioning
confidence: 99%